Kinetic modelling characterization of cellulose modified surface for methylene blue removal from aqueous media - Siti Maizatul Ameera, Azhar; Ahmad Salihin, Samsudin; Wan Norfazilah, Wan Ismail; Nurlin, Abu Samah (John Wiley & Sons, Inc., 2021)
In this work, commercial cellulose was modified with allylthiourea (Cel-AT) to remove methylene blue (MB) from aqueous solution. Characterization study include FTIR analysis along with UV spectrophotometer. A variety of physico-chemical properties such as kinetic, total sorption capacity loaded and pH effect by using Cel-AT sorbent has been carried out. The main finding was the adsorption total capacity of Cel-AT for MB was 3 times more than commercial cellulose (Cel) when the concentration of MB increase in batch mode. In kinetic study, the MB removal efficiency was at 90% after 5 min of removal using Cel-AT as a sorbent and Cel-AT fulfil pseudo second order of reaction. The optimum MB removal is at pH 11 with 95% of removal. There was spectral peak was observed in the spectrum of FTIR and it has been addressed accordingly. As a conclusion, the suggested method improved the quality of MB sorption onto the Cel-AT in terms of contact time and less laborious.